Antara Etnosentrisme dan Demokrasi: Konflik Etnis Dayak-Madura - Rifqi Hamdani (Jurnal Mengkaji Indonesia, 2022)
Abstract: The purpose of this article is to discuss the issue of ethnocentrism and democracy in Indonesia with case studies in two regions. Firstly, ethnocentrism as the root and source of conflict between ethnic Dayak and Madurese in Sampit, Central Kalimantan Province. Purpose: This article aims to discuss the issue of ethnocentrism in the Dayak and Madurese conflict. Design/Methodology/Approach: The research method used is qualitative research. By using a descriptive approach and data collection techniques using literature study. Findings: The conflict between Dayak and Madurese was caused by the sentiments of the two ethnicities. Ethnic differences are used as sentiments to compete in various aspects of social, economic, and, politics. Ethnic differences and diversity that are expected to go hand in hand and complement each other with the democratic system in Indonesia still reap many problems. The democratic system seems to open space for the emergence of inter-ethnic conflicts. This is certainly a challenge for the Indonesian people. The government needs to always encourage and open space to conduct political socialization to all Indonesian people and community or ethnic groups, especially those related to the values of nationalism, tolerance, and Indonesian unity. Originality/Value: Many have discussed issues related to ethnocentrism, both Dayak and Madurese conflicts. But this research is more directed at the issue of ethnocentrism.